Pengaruh Fomo, Review Konten Kreator, dan Live Shopping terhadap Perilaku Konsumtif Generasi Z Muslim Pengguna Tiktok - Radiah Aszahrah; Herlina Yustati; Esti Alfiah (Universitas Islam Lamongan, 2026)
Abstract: The rapid development of digital technology and social media, especially TikTok, has significantly influenced the consumer behavior of Generation Z. Psychological factors such as FOMO, as well as social media features such as Content Creator Reviews and Live Shopping have become important factors that encourage individuals to make unplanned purchases, which have the potential to cause consumer behavior. This study aims to determine the effect of FOMO, content creator reviews, and live shopping on the consumer behavior of Muslim Generation Z TikTok users in Bengkulu City. This study uses a quantitative approach with an associative research type. Data analysis was carried out through validity and reliability tests, classical assumption tests, and linear multiple regression analysis. Hypothesis testing used t-test, F-test, and coefficient of determination using SPSS 27 software. The number of samples in this study was 100 respondents, with data collected through a Likert-based questionnaire. The results showed that FOMO, content creator reviews, and live shopping had a positive and significant effect on consumer behavior. Simultaneously, the three independent variables significantly influenced consumer behavior, contributing 85.2% (R² = 0.852), while the remaining 14.8% was influenced by factors outside the research model. These findings highlight the crucial role of digital factors and social media in shaping the consumption patterns of Generation Z Muslims. Keywords: FOMO; content creator review; live shopping; consumptive behavior; Generation Z.